Evaluation of the Effect of Tagetes erecta Leaves Hydroalcoholic Extract on Blood Clotting Time - Roy , Sourav; Majumdar, Mrityunjoy; Roy, Prodip; Saha , Sanjoy; Das , Suranjanaa; Dey , Mon; Porel, Pratyush (Journal for Research in Applied Sciences and Biotechnology, 2023)
People were afflicted with a variety of illnesses prior to the revolution, and there was no access to medications sufficiently, at that time herbal agents fulfilled the demand for medications. In these modern days due to the huge side effects as well as drug resistance of marketed drugs, the demand for herbal medicines is increasing. We are all busy in our lives these days, we are traveling here and there to maintain our social duties. Due to this, the number of accidents is increasing around us. When a blood vessel is injured, blood clotting, or coagulation, is a crucial process that reduces excessive bleeding. So, the drugs that are able to reduce clotting time are essential for us. In this research we evaluated the blood clotting effect of two different doses (250mg/kg and 500mg/kg) of Tagetes erecta leaves hydroalcoholic extract on the albino wistar rat, and compared the effect with a marketed standard drug Tranexamic Acid (Pause 500 mg).